A insurreição no agora: comuna, novas formas-de-vida e a desinstituição da representação política - Rodrigo Wagner Santos Ribeiro Filho (2021)
The need for a rupture with the State-capital form is a marker of the democratic-radical struggles that have come to life in recent centuries. These insurrectional events carry connections and identifications among themselves, making up an underground trail of collective potencies – albeit briefly lived, but that light the way to other possible realities. Based on the discussions developed by the Invisible Committee collective, we intend to think about practices that allow the emergence of new forms of life in the present, identifying possibilities of ruptures with the devices that intend to consolidate themselves as the reason for the modern world, as political representation, the State and the individual. To reflect on the disinstitution of the devices that support the current state of things, the work begins with a radical critique of what we call representative democracy, the predominant form in Western States; then, through the study of a mosaic of past and present struggles, with the aim of pointing out precarious and changing directions for the subversion of the current world. Finally, we bet on the commune as a possible name for everyday insurrections, as events of common experience that put into action a free and powerful game between the singularities and their surroundings, escaping from the determinations of the capital-State and opening, by force, doors to other worlds.